Simulasi Komunikasi Data Altitude dan Airspeed Pesawat pada ARINC 429 Menggunakan Visual Basic 2010 Express - Krisna, Angga Leo Anggara; Astuti, Yenni; Dermawan, Denny (AVITEC, 2019)
Communication is the process of delivering information from a node to other nodes. In general, communication in the form of voice and data must be understood by both nodes. Flight data communication is used for pilots to collect information from the devices used. In this research, ARINC 429 data communication system is simulated using visual basic 2010 express. By using a GUI, the input data is obtained from the flight radarpro24 application. The data are representation of altitude and airspeed of Lion Air commercial flight JT922. The 32 bits of binary data are converted into decimal format. It was concluded that the altitude and airspeed data can be read and analyzed using this format.